Platelet monitoring for PCI - Capodanno, D.; Angiolillo, D. J. (Hämostaseologie, 2009)
Despite the clinical benefit associated with the combined use of aspirin and clopidogrel in patients with acute coronary syndrome or those undergoing percutaneous coronary intervention, a considerable interindividual variability in response to these drugs have been consistently reported. There is a growing interest on applying platelet functional tests with the goal of identifying patients at increased risk of recurrent ischaemic events and potentially tailoring antiplatelet treatment regimens.This manuscript will review the state of the art on the most commonly available platelet functional tests, describing their advantages and disadvantages and exploring their applicability in clinical practice.
Keywords: Platelet functional test; percutaneous coronary intervention; platelets